The diffusion and transformations of left-hand path religions in the contemporary popular culture - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2011)
In this article some features of the present-day (late 20th–early 21st c.) pop-culture, concretely cinematography, are analyzed for phenomena which can be interpreted as an ongoing transformation of normative morality, religious doctrines and ritual taboos of established religions on the ground of doctrines, practices and symbolism of modern (late 19th–20th c.) occult movements. The author argues that these phenomena are part of wider cultural and religious processes, i.e. of diffusion in public, secular, and also new religious and spiritual movements of what in this study was formulated as the “left-hand paths in religions”, the processes that perform a “reevaluation of values” of given society, grounded in particular established religion and religious identity, reevaluation of established moral norms and ritual taboos as at certain extent “destructives”. To achieve this goal the author has formulated a theoretical tool for analysis of general phenomena in religions as “left-hand path in religions” on the basis of Andree Padoux’s descriptions of “lefthand path” in Hindu religions, and which can be formulated as follows: left-hand path in religions – are elitist religious texts and practices that are destined not to eliminate norms of morality and ritual taboos of established religion, as far as they are acceptable for society in general as the basis for social order, but to achieve some goals that this established religion is supposed incapable to help to achieve in established manner, and only knower and practitioner of doctrines, rituals and other practices (that sometimes transgress established ones) is able to achieve those goals. In this study the author has explored the usage and conceptions of the term “left-hand path” in some modern Western occult movements; also the author has classified present-day fantasy cinematography in five groups, each according to the relationship to various kinds of “paranormal” realities. One of the groups is composed of movies in which symbols, practices, doctrines of modern “Western” occult movements (i.e. of Thelema, Aleister Crowley, LaVey) are exploited. That results in the subversion of values and ritual taboos of established religions (most often Christianity, and especially Catholicism). The diffusion of the “left-hand path” in popular and secular area of society becomes in a certain degree the “right-hand path”.